Intersections of Home, Health, and Social Engagement in Old Age: Formal Volunteering as a Protective Factor to Health After Relocation. (January 2019) - Gonzales, Ernest; Shen, Huei-Wern; Perry, Tam E.; Wang, Yi
This study aims to further our understanding of formal volunteering as a protective mechanism for health in the context of housing relocation and to explore race, gender, and education as moderators. A quasi-experimental design evaluated the effects of volunteering on older adults' health (self-report health, number of instrumental activities of daily living [IADLs], and depressive symptoms) among individuals who relocated but did not volunteer at Time 1 ( N = 682) in the Health and Retirement Study (2008–2010). Propensity score weighting examined health differences at Time 2 between 166 volunteers (treated) and 516 nonvolunteers (controlled). Interaction terms tested moderation. Individuals who moved and engaged in volunteering reported higher levels of self-rated health and fewer IADL difficulties compared to the control group. Race moderated the relationship between volunteering and depressive symptoms, while gender moderated the relationship between volunteering and self-assessed health. Formal volunteering protects different dimensions of health after relocation. Volunteering was particularly beneficial for females and older Whites.